Irrigation intervention: a strategy for conserving biodiversity and improving food security in Royal Chitwan National Park buffer zone, Nepal - Adhikari, K.R.; Tan, Y.C.; Lai, J.S.; Pant, Dhruba (Wiley, 2009)
Technical interventions have not always led to expected outcomes when attempting to achieve a balanced growth between natural resource development and food production, particularly in the context of Third World countries. In Royal Chitwan National Park (RCNP) buffer zone, Nepal, farmers' perceptions were used to evaluate how irrigation resource development and the method of water sharing have increased household food security and reduced pressure on natural resources of the park. The findings indicate that with some variations between communities, increased water availability and reliability through irrigation development have improved crop diversity, cropping intensity, food sufficiency, and economic return to farmers. Community attributes such as leadership and dynamics were, among others, the decisive factors that determined the degree of success of the government development intervention programme in the buffer zone. Small landholders and low-income groups in dry areas perceived that they received greater benefits from micro-groundwater pumping schemes. However, many rural poor inhabitants in the area still lack access to these resource opportunities. We observed that Park and People, a government programme, successfully improved public relations and helped create awareness in this buffer zone. However, grievances persist among other water user groups in the upstream part of the Rapt River where a water sharing mechanism needs to be defined between water user associations for crop production and maintenance of biodiversity of the national park.